Unjuk Kinerja Mesin Pemanen Padi (Combine Harvester) Yanmar AW70V di Lahan Sawah Kecamatan Seputih Mataram Kabupaten Lampung Tengah - Asmara, Sandi; Kuncoro, Sapto; Suharyatun, Siti; Hermawan, Dedi (abe.fp.unila.ac.id, 2024)
Combine Harvester Yanmar AW70V, is religion which helps the process of harvesting rice from cutting, channeling, threshing, separating the grain to cleaning the grain while walking in the field so as to shorten the harvesting time. The purpose of this study was to test the performance of the Yanmar AW70V Combine Harvester machine used for rice harvesters in Seputih Raman District Central Lampung Regency. This test includes actual work speed, field capacity and field efficiency as well as harvesting capacity, losses or loss values, and fuel consumption of the Yanmar AW70V Combine Harvester machine. This research method uses experimental methods in collecting data which is then analyzed and presented in tabular form and processed descriptively. The performance of the Yanmar AW70V Combine Harvester harvesting machine on the land produces an actual working speed of 1,19 m/s or 4,284 km/hour, theoretical field capacity 0,899 Ha/hour, effective field capacity 0,39 Ha / hour and field efficiency of 43%, losses or loss value of 282 kg or 6,9%, and fuel consumption of 19,8 liters/Ha. Keywords: Machine Combine Harvester, Performance Test, Yanmar AW70V